Yield Strength Analysis by Small Punch Test Using Inverse Finite Element Method. (2015) - Yang, S.S.; Ling, X.; Qian, Y.; Ma, R.B.
Abstract: Considering the change of material behavior in in-service component due to temperature, loading and irradiation, several micro-specimen techniques have been proposed to describe deformation and fracture behaviors of materials under different conditions. This paper investigates the mechanical characterization of materials by the experimental and numerical method of small punch test. A two-dimensional finite element model was established to simulate the deformation behavior of X80. The resulting Load-Displacement curve contains key information about the mechanical properties of the tested materials. Thus, an application of inverse finite element method was used in the investigation of mechanical properties of materials which have been tested by small punch test. The difference between experiment and simulation curves was defined as objective function based upon the calculation model established by ABAQUS and MATLAB procedure. Finally, the estimated results suggested confidence in the analysis of the inverse finite element method for material's yield strength.